2012
DOI: 10.1136/emermed-2012-201642
|View full text |Cite
|
Sign up to set email alerts
|

Reported medication events in a paediatric emergency research network: sharing to improve patient safety

Abstract: ME reporting by the system revealed valuable data across sites on medication categories and potential human factors. Harm was infrequently reported. Our analyses identify trends and latent systems issues, suggesting areas for future interventions to reduce paediatric ED medication errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 26 publications
1
51
0
7
Order By: Relevance
“…In Shaw et al's study [19] investigating reporting of 597 medication errors in pediatric emergency rooms, the rate of near miss errors was the lowest (30%). In Sears, Pallas, Stevens, and Murphy's study, [20] of the 372 reported errors, 127 were potential errors in other words near miss errors.…”
Section: Discussionmentioning
confidence: 99%
“…In Shaw et al's study [19] investigating reporting of 597 medication errors in pediatric emergency rooms, the rate of near miss errors was the lowest (30%). In Sears, Pallas, Stevens, and Murphy's study, [20] of the 372 reported errors, 127 were potential errors in other words near miss errors.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria das pesquisas sobre o tema proposto foi realizada no exterior, com destaque para Estados Unidos da América (11)(12)(13)(14)(15)17,(22)(23)25,(27)(28)(29)(30)(31)33) . Com relação ao ano de publicação, há predomínio a partir do ano de 2011 (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(31)(32)(33)(34)(35) .…”
Section: Web Of Science 2016 Canadá Journal Of Evaluation In Clinicalunclassified
“…A maioria das pesquisas sobre o tema proposto foi realizada no exterior, com destaque para Estados Unidos da América (11)(12)(13)(14)(15)17,(22)(23)25,(27)(28)(29)(30)(31)33) . Com relação ao ano de publicação, há predomínio a partir do ano de 2011 (9,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(31)(32)(33)(34)(35) . Unidades pediátricas gerais aparecem como maior foco dos estudos (66,6%), entre elas, unidades de internação clínica e unidades cirúrgicas (9,(11)(12)(13)(17)(18)(19)(20)(21)(22)(23)25,(27)(28)(29)(31)…”
Section: Web Of Science 2016 Canadá Journal Of Evaluation In Clinicalunclassified
See 2 more Smart Citations